Isoenzymatic variability in populations of Lupinus from Beira Interior - Frederico, A.M. (2011)
Isoenzyrnatic studies were performed in order to study the varia¬bility of Lupinus spp. populations from Beira Interior region. Thirty accessions of Lupinus (L. luteus, L. albus, L. angustifoius and L. Hispanicus) from Beira interior region were studied. The zymograms were obtained, by poliacrilamide gel ele¬ctrophoresis (PAGE). Extracts were prepared from young leaf and cotyledons tissues. Four enzyme systems were studied: aspartate aminotransferase (AAT), esterase (EST), acid phos¬phatase (ACT) and malate desidrogenase (MDH). Isoenzyme polymorphisms were found for all the enzyme sys¬tems studied. The comparative analysis of AAT and MDH zymograms show imerspecific variation and made it possible to identify the four species studied. Significant intraspecific varia¬tion was found in EST and ACP zymograms; however intrapopu¬lational variation was also detected and the different popula¬tions could not be distinguished inside each species. The existance of a greater genetic proximity between L. luteus and L. hispanicus was detected.